Exploring Teachers' Perceptions and Practices of Teaching Reading Comprehension in Selected ESL Rural Ghanaian Junior High Schools - Joshua Kwabena Nbiba Bintul; Isaac Owusu Nyarko; Anafo Cephas; Michella Atabaso Otoo (Journal of Applied Linguistics, 2026)
Reading comprehension in Ghanaian Junior High Schools remains a major concern despite long-standing reforms. This study examined teachers’ perceptions and classroom practices in rural schools and explored how these shape comprehension instruction. Schumann’s (1978) Acculturation Model guided the study and positioned comprehension as a social process influenced by learners’ cultural and linguistic alignment with English. A qualitative approach using a narrative research design was employed. Fourteen English language teachers from rural schools in the Nkwanta North District were purposively selected. Data came from interviews, observations, and documents, and was analyzed thematically. Findings revealed two main perceptions emerged. Many teachers viewed comprehension as a mechanical and exam-driven task. Others framed it as a meaning-making act linked to students’ social worlds. Classroom practices reflected these positions. Most lessons focused on literal recall and teacher-led routines. A few teachers used dialogue and familiar cultural examples to support deeper reading. Contextual pressures such as scarce materials, rigid syllabi, and examination demands shaped these choices and limited pedagogic flexibility. The study concludes that comprehension improves when teachers act as cultural mediators who connect learners’ lived realities with English texts. It calls for teacher development that supports culturally grounded and interactive reading practices in rural Ghana. Keywords : Reading Comprehension; Teachers’ Perception; Reading Instruction